Preparing ESL Teachers for a Communicative Curriculum American Style - Goodman, Pearl ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
A practicum assignment designed for master's-level teacher trainees in the field of English as a second language is presented with a sampling of the results. The assignment was to design a communicative syllabus to cover three 50-minute periods and focus on three of these areas: language arts, language for a purpose, personal second language use, theater arts, and language beyond the classroom. The three areas chosen were to be interrelated but independent in the lessons designed by the trainees. Each class period was to be outlined, with the purposes and goals listed. Five trainee-designed units are included, with notes on their approaches to particular problems or needs. (MSE)
ERIC Note: In: Savignon, Sandra J., Ed. and Berns, Margie S., Ed. Communicative Language Teaching: Where Are We Going? Urbana, Language Learning Laboratory, University of Illinois at Urbana-Champaign, 1983; see FL 016 358.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Behavioral Objectives; Communicative Competence (Languages); Course Content; English for Special Purposes; English (Second Language); Graduate Study; Higher Education; Instructional Materials; Language Arts; Language Teachers; Lesson Plans; Practicums; Second Language Instruction; Teacher Education; Teacher Education Curriculum; Theater Arts; Reports, Descriptive; Guides, Classroom -- Teacher; Journal Articles